Budaya Bertanya Sebelum Membaca: Tantangan Literasi di Media Sosial - Saskia Dea Astrina Situmeang; Zaskia Margaretha Komoyap; Putri Amiwati Harianja; Sinta Syabilla; Nabila Dwi Lestari; Gideon Waruwu; Hugo Alfredo Sinaga (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Social media has become the primary source of information for society, but easy access is not accompanied by adequate digital literacy skills. this study aims to analyze the phenomenon of “asking before reading” as a challenge of literacy on social media. the method used is a literature study with secondary data from scientific journal references and screenshots of user comments on instagram, tiktok, and facebook showing behavior of asking questions without reading the caption first. the results show that the habit of asking before reading is triggered by instant culture, dominance of visual content, and low reading interest. the impacts are decreased critical thinking skills, increased risk of misunderstanding, and spread of unverified information. the conclusion of this study confirms that the phenomenon reflects low digital literacy in society. the proposed solutions are improving digital literacy by encouraging users to read post descriptions, the role of educational institutions in instilling critical thinking from an early age, and clearer content from content creators and platform managers.